(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
Spiritual culture creates a special world of values, forms and complies with human intellectual and sacral demands. Spiritual values become special social and cultural vectors creating moral and spiritual base of national self-identity. Sacred sphere and spirituality encoding refers to the standard expressions of national ideological system. Language area as a coded system of axiological concepts and meanings of decoding reveals a nation’s worldview. Deep-seated perception of culture as a semiotic system becomes comprehensible via cultural code. This provides depiction of information transfer, processing, preservation within sign systems that cultural codes are. In the study of codification, spiritual code, which makes for moral values and standards, fixed in language, holds a specific place. Spiritual code of Ukrainian culture is a value oriented linguistic and philosophical category, which absorbs millennial folk wisdom imperative and philosophical foundations of Ukrainian nation worldview and ideology. Spiritual code represents axiology code that displays a set of moral values, ideals, categories and standards. Verbal expression of Ukrainians’ spiritual code is illustrated in idiomatic Ukrainian. The most powerful complier of the above-mentioned mechanisms is a corpus of precedent phenomena in language and paroemiological clichés in particular. As well as space of universal spiritual culture, the spiritual continuum of Ukrainian heritage always contains the vertical, which was segregating sacredness and commonness, earthly and heavenly life, up and down, good and evil. Paroemic clichés being semiotic signs broadcast social and cultural vectors of the modern Ukrainian nation. These vectors are focused on pragmatic attitudes to the active society existence and implement moral and ethical outlook priorities of national self-consciousness and self-identity among the all Ukrainians. The entire paramiology is based on contrast of good and evil. The oppositional technique of logical interdependence upbuilding in paroemias elicits dominance of counterpositions in establishment of native speakers’ linguistic consciousness and subconsciousness as it highlights semantic opposition of the selected moral and ethical elements. Categories “good” and “evil” as basic representatives of a spiritual code estimate the whole human existence. This very binary opposition gives grounds for nominating categorical oppositions and vectors of Ukrainian nation’s spiritual priorities.